2005
DOI: 10.2300/acari.14.127
|View full text |Cite
|
Sign up to set email alerts
|

Lethal effects of two types of oxygen absorbers on three house dust mites, Dermatophagoides farinae, D. pteronyssinus and Tyrophagus putrescentiae (In Japanese)

Abstract: Lethal effects of two types of oxygen absorbers on three house dust mites, Dermatophagoides farinae, D. The lethal effects of two types of oxygen absorbers on the house dust mites, Dermatophagoides farinae, D.pteronyssinus and Tyrophagus putrescentiae were studied. The mortality obtained after 48 hours in an air-tight container with iron (Fe)-type oxygen absorbers was 100% for D. farinae, and D. pteronyssinus, but was not 100% for T. putrescentiae. On the other hand, the mortality obtained after 72 hours in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…It has been reported that food preservation with a deoxygenating agent inhibits the decrease in fatty acids (Kohama et al, 2005) and the generation of insect pests (Kamezaki et al, 2005). In addition, the storage of rice with nitrogen-and carbon dioxide-atmosphere packages has been studied (Roberts, 1961;Yanai et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that food preservation with a deoxygenating agent inhibits the decrease in fatty acids (Kohama et al, 2005) and the generation of insect pests (Kamezaki et al, 2005). In addition, the storage of rice with nitrogen-and carbon dioxide-atmosphere packages has been studied (Roberts, 1961;Yanai et al, 1979).…”
Section: Introductionmentioning
confidence: 99%